Triaxial experiments on the mechanical properties of hydrate-bearing marine sediments of South China Sea. (November 2016) - Luo, Tingting; Song, Yongchen; Zhu, Yiming; Liu, Weiguo; Liu, Yu; Li, Yanghui; Wu, Zhaoran
Abstract: In this paper, a series of experiments was conducted on remoulded hydrate-bearing marine sediments from a gas hydrate core drilling site located in the Pearl River Estuary of the South China Sea. The composition and particle size distribution of marine sediments were analysed, and triaxial loading experiments were performed to study the mechanical properties of hydrate-bearing marine sediments. The strength properties of hydrate-bearing marine sediments were compared with those of hydrate-bearing kaolin clay, ice-marine sediment mixtures and hydrate-dissociated marine sediments under the same porosity (40%), temperature (8 °C), confining pressures (2, 3, and 4 MPa), and strain rate (1%/min) conditions. Several important results were obtained: The composition and particle size distribution analysis indicated the marine sediment and kaolin clay are both sandy clays, and the stress-strain behaviours and strength properties of hydrate-bearing marine sediments are similar to those of hydrate-bearing kaolin clay. Under different confining pressures, the failure strengths of all ice-marine sediment mixtures were lower than those of methane hydrate-bearing sediments, confirming that hydrate particles enhance the cementation of sediment particles. Hydrate dissociation leads to strength reduction of gas hydrate-bearing marine sediments, as was demonstrated in our previous research of hydrate-bearing kaolin clay. Through the analysis of Mohr circles and failure envelopes of three types of mixtures under different confining pressures, it can be inferred that the cohesive strength played an important role in the failure strength of hydrate-bearing marine sediments following hydrate dissociation. Highlights: Triaxial strength experiments were conducted on hydrate-bearing marine sediments of South China Sea. Strength property of hydrate-bearing marine sediment was found to be similar to hydrate-bearing kaolin clay. Hydrate between sediment particles enhances the cohesion of sediment. Cohesion reduction accompanying with hydrate dissociation greatly affects the failure strength of hydrate-bearing sediment.